Let's solve your equation step-by-step.
25m+100−24m−75=68
Step 1: Simplify both sides of the equation.
25m+100−24m−75=68
25m+100+−24m+−75=68
(25m+−24m)+(100+−75)=68(Combine Like Terms)
m+25=68
m+25=68
Step 2: Subtract 25 from both sides.
m+25−25=68−25
m=43
Answer:
m=43
Answer:
(4x + 1)(x² - 2)
Step-by-step explanation:
Given
4x³ + x² - 8x - 2 ( factor the first/second and third/fourth terms )
= x²(4x + 1) - 2(4x + 1) ← factor out (4x + 1) from each term
= (4x + 1)(x² - 2)
Answer:
looks hard
Step-by-step explanation:
ndjwdfhewgifgwhcvw
Answer:
here look for it there is a sol
Step-by-step explanation:
https://www.careerlauncher.com/cbse-ncert/class-9/Math/CBSE-SurfaceAreasandVolumes-NCERTSolutions.html